Design of an Android application for autonomous control of mobile robot - Top, Ahmet; Gokbulut, Muammer (My University, 2024)
In this study, a mobile application (app) for Android devices (ADs) is designed to gather robot data and supply the reference values needed for the autonomous operation of mobile robots intended for various uses. Robot control settings can be supplied with any AD using this application; no further hardware or computer is needed for robot control. Beyond providing manual control, the application also has an interface for autonomous control. It allows the robot to be directed to certain locations by sending it three coordinate points and the approach distance. Furthermore, as the robot moves, real-time data can be received by Bluetooth (BT) on the AD, and the robot's current position is shown on the device's screen. To demonstrate the efficacy of the study, control of the robot with Proportional-Integral-Derivative (PID) and Fuzzy logic controller (FLC), whose prototype are carried out, was performed per the references received from the AD. Meanwhile, real-time data about the robot was gathered on the same AD with the Excel file extension, mailed to the PC, and data graphs were created. The study has demonstrated that ADs may be used for both manual and autonomous control of robots.
Keywords: Android application; MIT App Inventor; Robot control